2014
DOI: 10.1080/10550887.2014.882730
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Illegal Acts to Pathological Gambling Diagnosis: DSM-5 Implications

Abstract: The purposes of this study were to examine the specific contribution of illegal acts to the diagnostic criteria of pathological gambling, to assess the possibility of differential item functioning across patients' sex and age, and to explore the existence of different clinical phenotypes based on the presence of illegal acts. The sample consisted of 2,155 patients seeking treatment for pathological gambling at the University Hospital of Bellvitge in Barcelona, Spain. The illegal acts item did not show differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…In her view, illegal behavior was a consequence of severe gambling disorder rather than a diagnostic symptom. The illegal-acts criterion in the DSM-4 included "forgery, fraud, theft, or embezzlement to finance gambling" (American Psychiatric Association 2000, 674), and was introduced as a diagnostic criterion to establish a clear distinction between pathogenic elements and ensuing gambling-disordered behaviors (see also Granero et al 2014). Most clinicians recognized that the recalibration of diagnosis could affect the legal definition of gambling.…”
Section: A Clinical Economy Of Speculationmentioning
confidence: 99%
“…In her view, illegal behavior was a consequence of severe gambling disorder rather than a diagnostic symptom. The illegal-acts criterion in the DSM-4 included "forgery, fraud, theft, or embezzlement to finance gambling" (American Psychiatric Association 2000, 674), and was introduced as a diagnostic criterion to establish a clear distinction between pathogenic elements and ensuing gambling-disordered behaviors (see also Granero et al 2014). Most clinicians recognized that the recalibration of diagnosis could affect the legal definition of gambling.…”
Section: A Clinical Economy Of Speculationmentioning
confidence: 99%
“…Others [10–11] highlight the conceptual role of illegal acts as a diagnostic criterion and whether these behaviors represent a core component of the underlying psychopathology or rather represent a possible consequence of the disorder. Consequences of mental disorders are less likely to be useful diagnostic indicators, especially if they occur further into disease severity or disease progression as appears to be the case for gambling-related illegal acts.…”
Section: Elimination Of Illegal Acts Criterionmentioning
confidence: 99%
“…Clinicians likely do see higher proportions of treatment-seeking gamblers reporting illegal acts (23–41%) [10, 12, 16–17], especially as compared to population-based samples of gamblers (0.1–0.4%) [6, 8] and even community samples of those meeting DSM-IV gambling criteria (19%) [7]. Gamblers seeking treatment tend to be higher on the severity spectrum, and, as noted above, illegal acts are more prevalent among these higher severity gamblers.…”
Section: Elimination Of Illegal Acts Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also lead to legal consequences, such as check forgery, embezzlement, theft, larceny, armed robbery, bookmaking, hustling, running con games, fencing stolen goods, loan fraud, tax evasion, burglary, pimping, prostitution, and sale of drugs ( Lesieur & Rosenthal, 1991 ). Gambling-related illegal activities were considered as a diagnostic criterion until the DSM-IV-TR ( APA, 2000 ) and several epidemiological studies demonstrated its almost exclusive relationship with the most severe forms of the disorder ( Carragher & McWilliams, 2011 ; Granero et al., 2014 ; McBride, Adamson, & Shevlin, 2010 ; Strong & Kahler, 2007 ). The prevalence of illegal acts in individuals with gambling disorder ranges from 14% to 30% ( Granero et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%